IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN PRESTASI SISWA - Roy Chrisnando Subagio; Burhanuddin Burhanuddin; Imron Arifin; Roy Chrisnando Subagio; Burhanuddin Burhanuddin (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This study aims to describe school-based management in improving student achievement where the main focus in this study is the condition of student achievement, both academic and non-academic through school-based management. This research uses a qualitative approach with case study research. This research was conducted at SDN Tanjungrejo 4 Malang City. Data collected using interview techniques, observation and documentation. Then analyzed through an interactive process through the stages of reduction, presentation and verification of data. The results of this study indicate that school-based management programs can have an impact on improving student achievement through an effective management process.